Implementation of the ADDIE Training Model to Strengthen the Pedagogical Competence of Productive RPL Teachers at SMK Telkom 1 Medan - Taufiq Ramadhani; Yuniarto Mudjisusatyo; Aman Simare-mare (Asia Pacific Journal of Management and Education (APJME), 2025)
Teacher professionalism is a key factor in improving the quality of education, especially in Vocational High Schools (SMK). However, many teachers still face challenges in mastering pedagogical and professional competencies, as seen in the Software Engineering (RPL) program at SMK Telkom 1 Medan. This study aims to analyze the development, feasibility, and effectiveness of ADDIE model training management in enhancing the professional competence of productive RPL teachers at SMK Telkom 1 Medan. The research employs a descriptive approach with stages of needs analysis, design, development, implementation, and evaluation. The results are expected to contribute to the development of structured and sustainable teacher training models and serve as a reference for schools in improving teaching quality and teacher professionalism